Noninvasive estimation of the maximal lactate steady state in trained cyclists - Swensen, T. C.; Harnish, C. R.; Beitman, L.; Keller, B. A. (Medicine & Science in Sports & Exercise, 1999)
Our data suggest that 5-km TT (time trial) cycling velocity, as measured on a windload simulator, may be used to estimate MLSS (maximal lactate steady state ) and the HR at MLSS for training purposes.